Workshop Penerapan Metode Finger Math dalam Meningkatkan Kemampuan Berhitung Anak di Lingkungan Kelurahan Cibabat - Agustianti, Rifka; Simangunsong, Herlina; Kadir, Iftitah Rahmi; Zukir, Muhammad (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The low ability of children to count and the lack of motivation to learn, especially in mathematics, is a separate homework for parents. In addition, learning methods that are less varied often make children feel bored. Therefore, a solution is needed to solve this problem, namely through a workshop program for parents, especially mothers, on how to accompany and teach their children who are at elementary school age about the use of the finger math method. In this activity, materials and socialization are provided on how to count using the finger math method and solving arithmetic problem applications, especially addition and multiplication operations, where all number operations can be completed using only the fingers. This activity has the aim of being an alternative variation of fun mathematics learning, fostering motivation to learn mathematics, improving children's numeracy skills, minimizing the use of calculating tools such as calculators and the like, and highlighting the role of mothers as the first madrasah for children in accompanying their children to learn, especially mathematics. Evaluation of community service activities is carried out at the end of the activity using a questionnaire and the results are concluded using pre-test and post-test.